Evaluation of Patient- and Family-Centered Care in a Paediatric Clinic in Turkey: a Qualitative Study - Lubna Qutranji; Burçin Yorgancı Kale; Hatice Ezgi Barış; Kübra Tezel Gökçe; Okan Çetin; Esra Yılmaz; Emine Nural Öztürk; Perran Boran (Çocuk Dergisi)
Objective: Patient- and family-centered care (PFCC) involves the engagement of both the patients and their families, considering them as an essential member of the healthcare team. The aim of this study was to evaluate PFCC experience of hospitalized children’s parents in our hospital, assess current areas of strength and identify areas for growth for future improvement. Material and Methods: The inclusion criteria for the study were parents of children who were hospitalized for at least three consecutive days. The data of 27 mothers, who were the child’s primary caregiver in the hospital, were collected through face-to-face interviews. Children using immunosuppressive treatment were excluded from the study. Interviews lasted between 20 and 30 minutes. Data were analyzed using thematic framework analysis. Results: Mothers reported both positive and negative experiences during their hospitalization period. One of the main findings of our current study was that Turkish parents usually do not prefer to take an active role during the decision-making process. However, they do expect to be fully informed about the disease, diagnostic procedures, treatment, and expected complications. Conclusion: It is important to emphasize the importance of comprehensive implementation of PFCC for better healthcare outcomes. Recommendation includes offering communication skills training and education to healthcare providers and starting initiatives to improve the hospitals’ environment.